2016
DOI: 10.1155/2016/2581061
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroabietic Acid Derivative QC4 Induces Gastric Cancer Cell Death via Oncosis and Apoptosis

Abstract: Aim. QC4 is the derivative of rosin's main components dehydroabietic acid (DHA). We investigated the cytotoxic effect of QC4 on gastric cancer cells and revealed the mechanisms beneath the induction of cell death. Methods. The cytotoxic effect of QC4 on gastric cancer cells was evaluated by CCK-8 assay and flow cytometry. The underlying mechanisms were tested by administration of cell death related inhibitors and detection of apoptotic and oncosis related proteins. Cytomembrane integrity and organelles damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Dehydroabietic acid exhibits some interesting bioactivities including moderate antibiotic activities against Bacillus subtilis and Staphylococcus lentus , as found in the present study and also cytotoxic activities as demonstrated for a derivative of dehydroabietic acid recently [21]. Our study showed that the exploration of anoxygenic phototrophic purple bacteria for the production of bioactive compounds should be taken into consideration for biodiscovery.…”
Section: Discussionsupporting
confidence: 80%
“…Dehydroabietic acid exhibits some interesting bioactivities including moderate antibiotic activities against Bacillus subtilis and Staphylococcus lentus , as found in the present study and also cytotoxic activities as demonstrated for a derivative of dehydroabietic acid recently [21]. Our study showed that the exploration of anoxygenic phototrophic purple bacteria for the production of bioactive compounds should be taken into consideration for biodiscovery.…”
Section: Discussionsupporting
confidence: 80%
“…This study also demonstrates, through the chemical analysis of the pinecone water extract, the presence of eight main compounds, which were identified as dehydroabietic acid ( 1 ), 15‐hydroxy‐7‐oxodehydroabietic acid ( 2 ), 7 β ,15‐dihydroxydehydroabietic acid ( 3 ), β ‐ d ‐glucopyranosyl labda‐8(17),13‐diene‐(15,16)‐lactone‐19‐oate ( 4 ), 7 α ,15‐dihydroxydehydroabietic acid ( 5 ), (+)‐(1 S ,2 S ,4 R )‐limonene‐1,2‐diol ( 6 ), sobrerol ( 7 ) and 4‐hydroxybenzoic acid ( 8 ). Among these compounds, dehydroabietic acid and its derivatives have been shown to induce potent antitumor activity . In addition, limonene and its metabolites, such as limonene‐1,2‐diol, have demonstrated chemopreventive and tumor‐suppressive effects when applied to a variety of tumor models, by attenuating the expression and/or farnesylation of cell growth‐associated small G proteins, such as p21 ras , and thereby inducing apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…[10] Especially, many DAA derivatives have been reported exhibiting prominent anticancer activity through various mechanisms such as inducing apoptosis, inhibiting metastasis and angiogenesis, inhibiting tyrosine kinase activity and matrix metalloproteinase activity. [11][12][13][14][15] Based on these findings, DAA derivatives present fascinating potential in the discovery of new anticancer agents.…”
Section: Introductionmentioning
confidence: 99%